2015
DOI: 10.1007/s11606-015-3200-2
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a CPR and Intubation Video Decision Support Tool for Hospitalized Patients

Abstract: BACKGROUND: Decisions about cardiopulmonary resuscitation (CPR) and intubation are a core part of advance care planning, particularly for seriously ill hospitalized patients. However, these discussions are often avoided. OBJECTIVES: We aimed to examine the impact of a video decision tool for CPR and intubation on patients' choices, knowledge, medical orders, and discussions with providers. DESIGN: This was a prospective randomized trial conducted between 9 March 2011 and 1 June 2013 on the internal medicine se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
116
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(141 citation statements)
references
References 28 publications
4
116
2
1
Order By: Relevance
“…8 More research on how to increase communication about end-of-life issues and improve the quality of that communication using methods that can be implemented in actual practice is greatly needed. The study by El-Jawahri and colleagues 4 is an important step in that direction and adds to a growing body of research that more and improved communication about these issues is possible, can be practically implemented and can improve outcomes. Future developments in decision support tools, such as interactive methods that can be incorporated into the electronic medical record in the course of clinical practice, 9 as well as through electronic patient portals and "living" documents that can evolve over time and go beyond preferences for resuscitation and intubation to address other elements of communication about serious illness, may help to advance care in these areas.…”
Section: Published Online April 18 2015mentioning
confidence: 94%
See 3 more Smart Citations
“…8 More research on how to increase communication about end-of-life issues and improve the quality of that communication using methods that can be implemented in actual practice is greatly needed. The study by El-Jawahri and colleagues 4 is an important step in that direction and adds to a growing body of research that more and improved communication about these issues is possible, can be practically implemented and can improve outcomes. Future developments in decision support tools, such as interactive methods that can be incorporated into the electronic medical record in the course of clinical practice, 9 as well as through electronic patient portals and "living" documents that can evolve over time and go beyond preferences for resuscitation and intubation to address other elements of communication about serious illness, may help to advance care in these areas.…”
Section: Published Online April 18 2015mentioning
confidence: 94%
“…The study by El-Jawahri and colleagues 4 has some limitations. The participants were mostly white; other patient groups should be studied since they may have different needs and preferences.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…One factor driving such complexity is the need to understand, incorporate, and integrate the values of patients, family members, and clinicians. In a randomized trial reported in this issue, El-Jawahri et al 4 evaluated an educational video that teaches medical inpatients about intubation and cardiopulmonary resuscitation (CPR). Based on a framework developed by co-author Angelo Volandes and popularized in his book (The Conversation, Bloomsbury, 2015), the videos were designed to help patients understand what to expect from these procedures.…”
mentioning
confidence: 99%